1993
DOI: 10.1111/j.1469-8986.1993.tb03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on electrodermal orienting reflexes to stimulus change and stimulus significance

Abstract: Skin conductance responses (SCRs) evoked by novel, signal, and frequent tone stimuli were measured in 20 male heavy smokers and 10 male nonsmokers over two sessions. All smokers abstained from smoking for 12 hr prior to each session. Half of the smokers smoked a cigarette of their preferred brand prior to SCR measurement in the first session, whereas the remaining smokers smoked in the second session. Nonsmokers did not smoke. Results combined across the two sessions indicated that abstinence was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…It would be appropriate to consider the possibility that variables characteristic of the ®rst session, such as the anxiety level or a greater interest and motivation in the novel experimental situation, may interact with the experimental treatment. Our results con®rm previous research which has also observed that the order of administration of the experimental treatment (smoking versus non-smoking) or the order of the presentation of the task can interact with speci®c eects of the treatment (Lyvers and Miyata, 1993;Petrie and Deary, 1989;Provost and Woodward, 1991). Nevertheless, another explanation of our data could be that the inhalation variables, which may play a role in determining smoke exposure, diered between the two sessions.…”
Section: Discussionsupporting
confidence: 80%
“…It would be appropriate to consider the possibility that variables characteristic of the ®rst session, such as the anxiety level or a greater interest and motivation in the novel experimental situation, may interact with the experimental treatment. Our results con®rm previous research which has also observed that the order of administration of the experimental treatment (smoking versus non-smoking) or the order of the presentation of the task can interact with speci®c eects of the treatment (Lyvers and Miyata, 1993;Petrie and Deary, 1989;Provost and Woodward, 1991). Nevertheless, another explanation of our data could be that the inhalation variables, which may play a role in determining smoke exposure, diered between the two sessions.…”
Section: Discussionsupporting
confidence: 80%
“…Evoked and spontaneous SCRs were also compared across caffeine user groups and consumption conditions to determine whether caffeine would affect such measures in line with previous findings for alcohol (Lyvers & Maltzman, 1991a) and nicotine (Lyvers & Miyata, 1993). Caffeine levels as low as those typically present in one cup of coffee have been shown to increase autonomic nervous system activity, resulting in a number of behavioural and physiological changes (Quinlan, Lane, & Aspinall, 1997).…”
mentioning
confidence: 74%
“…A fully between-subjects design was employed because of the strong effects of repeated testing on both WCST performance (Lyvers & Maltzman, 1991b) and SCRs (Lyvers, Boyd, & Maltzman, 1988), which would likely obscure caffeine effects or complicate their interpretation. T o qualify for inclusion in the study, participants were required to (a) be between the ages of 18 to 35 years; (b) be nonsmokers, to avoid nicotine effects on WCST and SCR measures (Lyvers & Miyata, 1993;Lyvers et al, 1994); (c) report typical caffeine intake that met the above criteria for either HCC or LCC; (d) have no prior history of treatment or arrest for illicit drug-or alcohol-related problems; and (e) normally consume no more than 14 standard alcoholic drinks per week. T o recruit subjects, flyers were posted on the campuses of Bond and Griffith-Gold Coast Universities and an email request was sent to all Bond students.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, there were no group differences in skin conductance. Since most of the participants were provided nicotine patches for the test session (61% and 54% of the propranolol and placebo group, respectively) and it is known that nicotine can alter skin conductance (Hori et al 1994; Lyvers and Miyata 1993; Reid et al 1998), it is possible that our efforts to minimize nicotine withdrawal may have compromised our ability to detect skin conductance differences (i.e., possibly by inflating measure variability).…”
Section: Discussionmentioning
confidence: 99%